A NARRATIVE REVIEW TO ACHIEVE NET-ZERO ENERGY HOMES IN MALAYSIA - Tan, Xian Yun; Mahyuddin, Norhayati; Mohamed Zaid, Suzaini (Journal of Surveying, Construction and Property, 2025)
Malaysia is heavily reliant on fossil fuels for electricity production but aims to reduce carbon emission intensity by 45% by 2030 and achieve net zero carbon emission by 2050. As residential buildings are one of the major energy consumers, achieving net-zero energy in homes is essential. This paper reviews the development of Net-Zero Energy Homes (ZEHs) globally and evaluates their relevance to Malaysia’s tropical climate. A narrative review approach was used to examine ZEH definitions, energy consumption factors, and green retrofitting strategies. The findings highlight the need for tailored policies and design standards suited to the local climate and socio-economic conditions. Recommendations are proposed to guide future development and policy actions for achieving energy-efficient residential housing in Malaysia.